2016
DOI: 10.1371/journal.pone.0155271
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Roma Minority Patients on Chronic Hemodialysis Therapy - A Romanian Multicenter Survey

Abstract: ObjectiveThe Roma minority represents the largest ethnic group in Central and South-East European countries. Data regarding the mortality in Roma hemodialysis subjects are limited. We evaluated the 3 year mortality of ESRD Roma patients treated with hemodialysis (HD).Study Design and SettingOur prospective cohort study included 600 ESRD patients on HD therapy recruited from 7 HD centers, from the main geographical regions of Romania. The median age of the patients was 56 (19) years, 332 (55.3%) being males, 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Roma ethnicity was shown to be an independent risk factor for mortality [ 8 ]. Similar to our results, the study of Gadalean et al also showed a significantly younger age of dialyzed Roma and a shorter dialysis history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roma ethnicity was shown to be an independent risk factor for mortality [ 8 ]. Similar to our results, the study of Gadalean et al also showed a significantly younger age of dialyzed Roma and a shorter dialysis history.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of some chronic diseases, such as diseases of the cardiovascular system, diabetes mellitus, obesity as well as kidney disease, has been reported in the Roma minority [ 2 , 3 , 4 , 5 , 6 , 7 ]. So far, Roma compared to non-Roma have been shown to have a 2.4-times higher likelihood of getting end-stage renal disease (ESRD) [ 3 ] and that their chances for survival on dialysis are lower [ 8 ]. Sudzinova found a similar result in a survival study on cardiovascular disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Roma therefore often neglect their medical needs, thereby leading to a higher incidence of morbidity and mortality from infections and chronic illnesses. 6 One multinational study has found that pregnant Romani women were unaware of their rights to care, and therefore had a higher rate of peripartum complications compared to non-Roma counterparts. 7 Similarly, the rates of teenage pregnancy, sexually-transmitted infections, and elective termination of pregnancy are much higher in Roma populations as a result of limited sexual education.…”
Section: Accessing Healthcarementioning
confidence: 99%
“…Health care staff members [ 48 ], officers [ 34 ], survey interviewers (with or without the support of a Roma community leader [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]), and parents of children [ 59 , 60 ] can perform this classification. Furthermore, the combination of self-reporting and a decisive external classification is also in practice [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The latter approach clearly shows that external classification is considered more reliable than self-reporting in certain cases.…”
Section: Introductionmentioning
confidence: 99%